2005
DOI: 10.1074/jbc.m506902200
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Zinc Transport Complexes of Cation Diffusion Facilitator Proteins Localized in the Secretory Pathway Operate to Activate Alkaline Phosphatases in Vertebrate Cells

Abstract: Zinc is an essential component for the catalytic activity of numerous zinc-requiring enzymes. However, until recently little has been known about the molecules involved in the pathways required for supplying zinc to these enzymes. We showed recently (Suzuki, T., Ishihara, K., Migaki, H., Matsuura, W., Kohda, A., Okumura, K., Nagao, M., Yamaguchi-Iwai, Y., and Kambe, T. (2005) J. Biol. Chem. 280, 637-643) that zinc transporters, ZnT5 and ZnT7, are required for the activation of zinc-requiring enzymes, alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
128
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 31 publications
8
128
2
1
Order By: Relevance
“…In contrast, the characteristics of the hetero-oligomerization between ZnT5 and ZnT6 and their functional orthologues are poorly understood (19,24,25). This is because ZnT5 and ZnT6 differ from other CDF/ZnT proteins in two important respects.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, the characteristics of the hetero-oligomerization between ZnT5 and ZnT6 and their functional orthologues are poorly understood (19,24,25). This is because ZnT5 and ZnT6 differ from other CDF/ZnT proteins in two important respects.…”
mentioning
confidence: 73%
“…Moreover, the functional yeast orthologues Zrg17p (Saccharomyces cerevisiae) and Zrg17 (S. pombe) show little homology to those of vertebrates. These discrepancies make it dif-ficult to understand the properties of these hetero-oligomers (19,24,25).…”
mentioning
confidence: 99%
“…Zn 2+ is loaded onto APs in the early secretory pathway that contains specific zinc transporters (ZnTs). Activation of human TNAP requires the presence of ZnT5/ZnT6 heterodimers and ZnT7 homooligomers [478,479]. It is thought that the activation takes place in two steps.…”
Section: Alkaline Phosphatasesmentioning
confidence: 99%
“…In the absence of ZnT5/ZnT6 heterodimers, the apo-form is degraded [481]. In contrast, the placental enzyme (PLAP) is constitutively expressed in the apo-form and trafficked to the plasma membrane in ZnT5/ZnT6-deficient cells [478,479], implicating that the activation processes of the two enzymes differ.…”
Section: Alkaline Phosphatasesmentioning
confidence: 99%
“…In the sense that ER function is dependent on zinc availability to provide zinc for incorporation into and folding of zinc metalloproteins (39), increased zinc may play a role in the restoration of ER homeostasis. In support of that notion, it has been shown that a supply of zinc to the early secretory pathway via ZnT5, ZnT6, and ZnT7 is essential for helping protein folding via zinc incorporation into alkaline phosphatases, which are zinc metalloproteins (40,41). The importance of an adequate zinc supply for protein folding was illustrated when TM-induced ER stress was exacerbated during zinc-deficient conditions in ZnT5 −/− /ZnT7 −/− cells (26).…”
Section: Discussionmentioning
confidence: 81%